Ag Behavior on TiN Thin Films for Decorative Coatings - Arruda, Antonio Carlos Santos de [UNESP] (2024)
TiN-Ag ceramic coatings deposited by magnetron sputtering on silicon wafers and AISI F138 stainless-steel substrates with different Ag concentrations were evaluated for their application as decorative coatings. The results obtained indicated an almost linear increase in the thickness and roughness of the film as a function of the increase in the silver content of the film. For Ag concentrations greater than (8.3 ± 0.5) at %, a matte/satin finish was observed, i.e., a dull surface, produced by the agglomeration of particulates and the increase in roughness, respectively, which was corroborated by SEM and AFM analyses. The EDS analyses indicated particles with a high concentration of silver, but the elements titanium and nitrogen were also observed, indicating the formation of the TiN-Ag coating. The L*a*b* parameters in the CIELab color space were evaluated. No major variations were observed for coatings A and B (Ag concentrations of (4.1 ± 0.4) and (6.3 ± 1.2) at %, respectively). When the Ag content increased substantially, there was a corresponding decrease in L* values, as well as a shift in red reflectance. Furthermore, unwanted changes in the visual appearance and resistance to accelerated corrosion (salt spray) were also analyzed, as these factors compromised the film’s aesthetics in decorative applications.